The Urgency of Establishing Regional Regulations in Southeast Sulawesi to Reduce the Increasing Number of Child Marriages - Isnayanti Isnayanti; Idris Saputra; Ilham (Simbur Cahaya, 2026)
Child marriage remains a serious problem in Southeast Sulawesi Province, despite Law Number 16 of 2019 raising the minimum age for marriage to 19 years. In 2024, 221 children were recorded as having married before age 19, of whom 85.5% were girls. This study aims to analyse the factors contributing to child marriage and the urgency of establishing a Regional Regulation as a preventive measure in Southeast Sulawesi. The study used a normative-empirical method, combining a review of laws and regulations with an analysis of empirical data on child marriage. The results show that child marriage is influenced by educational, economic, socio-cultural, customary law, technological developments, and promiscuity factors that lead to premarital pregnancies. The establishment of a Regional Regulation is urgently needed because national policies have not effectively addressed the socio-cultural characteristics of local communities. This study found that the Regional Regulation on the Prevention of Child Marriage needs to include provisions regarding prevention, supervision, assistance, and the involvement of various stakeholders in child protection. The research conclusion indicates that the Regional Government has the authority to establish Regional Regulations as a preventive legal instrument to strengthen child protection and reduce the number of child marriages in Southeast Sulawesi. The novelty of this research lies in the formulation of a substantive model of the Regional Regulation on Child Marriage Prevention that is tailored to the socio-cultural characteristics of the Southeast Sulawesi community.